Potential utilization of biodiesel as alternative fuel for compression ignition engine in Malaysia - Wahab, M. A.*; Ma’arof, M. I. N.*; Ahmad, I. N.; Husain, H. (IOP Publishing, 2017)
Biodiesel is a type of fuel which is derived from various sources of vegetable plants and waste fuels. Today, numerous biodiesels have been engineered to be at par or even better in term of performance in comparison to pure diesel. Therefore, biodiesel has shown a promising sign as one of the best candidate in overcoming total dependency on pure diesel. This paper gives review on various tests and experiments conducted on biodiesel in order to highlight the potentials given by this particular fuel. In addition, providing the supporting evidences to further endorse for a mass usage of biodiesel in Malaysia – simultaneously, driving the country to become a potential global biodiesel producer in the near future. The reviewed studies were obtained mainly via indexed journals and online libraries. Conclusively, every test and study for every blend of biodiesel had shown consistent positive results in regards to performance and in overcoming emission related issues. Thus, providing the evidence that biodiesel is highly reliable. Malaysia as a semi-agricultural nation could take the advantage in becoming one of the leading global biodiesel producers. Nevertheless, this will requires total cooperation of every concerned government bodies and authorities.